Facile synthesis and linker guided self-assembly of dendron-like amphiphiles. (22nd March 2019) - Ni, Bo; Qu, Haoran; Mao, Jialin; Bai, Ruobing; Zhang, Shuailin; Feng, Xueyan; Wesdemiotis, Chrys; Dong, Xue-Hui; Cheng, Stephen Z.D.
Abstract: In this work, we studied the linker effect on the nanostructures of a serious of specifically designed, functionalized polyhedral oligomeric silsesquioxane (POSS) based Dendron-like macro-isomers. The varying linkers between hydrophilic and hydrophobic POSS cages lead to topological isomers with identical composition but different molecular shapes. Their unique phase behaviors highlight remarkable effects of molecular architectures on the formation of nanostructures. Due to topological constraints, these macro-isomers assume either a fan- or a cone-molecular shape, which assembles into either hexagonally packed cylindrical phase (HEX) or Frank-Kasper A15 phase. This work provides guiding rules on designing precise molecular nanostructures with desired properties via linker engineering. Graphical abstract: Image 1 Highlights: Iterative method is a powerful way to synthesize macromolecules with precise structures. The shapes of linkers have great impact on the nano-structures formed. The rigidity of the hydrophobic part is the key of nano-structure transformation.